From Sevilla to Brussels: a Description of the Decision-Making Process from the Researcher's Bodily Experience While Navigating Risks in the Field - Ana Gabriela Hernandez (Conversations Across the Field of Dance Studies)
I am a Colombian bellydancer, psychologist, and activist specialized in peacebuilding. This essay constitutes an analysis of my fieldwork journey while pursuing a master's degree in dance anthropology in Europe. During my first fieldwork in Sevilla, Spain, I faced a risky situation that made me leave my first research destination to start a new project in Brussels, Belgium. In this essay, I describe in detail the circumstances in both locations and reflect on how my bodily experience and my cultural and academic background informed the decisions I made during fieldwork, helping me to develop an ethical methodology and setting a research project that guaranteed the three ethical minimums of dignity, autonomy, and freedom (Rodríguez, A. L., 2010) in the field. Martin (2019, p.5) explains how ethnographic research is a constantly improvised exercise similar to the one experienced in dance improvisation: “Like improvisation in dance, improvisation in an ethnographic encounter often means that there is a structure, task or idea motivating actions, it is not entirely random, but within the frame created there are many possibilities about how events might unfold.” Thus, the researcher’s bodily experience informs the decision-making process in the field; at the same time, it is determined by a frame that motivates the actions taken. In this case, the frame was determined by the ethnographic situation I was immersed in and the education I received regarding how to conduct ethnographic research. According to Hanson and Richard (2017), there are three “fixations” of contemporary ethnography; these are solitude, danger, and intimacy; Since I feel related to the fixations exposed, I begin by drawing attention to my body to claim my humanity and understand how my bodily experience influenced me to take ethical decisions for myself despite the ethnographic framework I was immersed in. Finally, I propose that improving the ethics within the field of anthropology requires high awareness and acknowledgment of the researcher’s humanity and vulnerability. This acknowledgment must be encouraged in the academic debate and included as part of academic writing. Thus, we can continue to construct safer and more ethical ethnographic research projects in the future.